Towards translation of environmental determinants of physical activity in children into multi-sector policy measures: study design of a Dutch project - van Oers Hans AM; van de Goor Ien AM; Aarts Marie-Jeanne; Schuit Albertine J (BMC, 2009)
Abstract Background Physical inactivity in children is a major health problem in The Netherlands as well as in many other Western countries. In addition to health promotion among parents and children, creating "active" neighbourhoods can contribute to the solution of this health problem. However, changing environmental characteristics is often the responsibility of policy sectors outside the Public Health domain. Therefore this project identifies and evaluates the possibilities of multi-sector policy measures to stimulate physical activity in children. Methods and design The project consists of quantitative as well as qualitative research methods and is conducted in four medium sized Dutch cities. To identify perceived environmental determinants of physical activity in children, a large scale health survey was conducted at 42 primary schools. Written questionnaires including topics on the children's physical activity behaviour (i.e. sports participation, outdoor play, active commuting, television watching and computer usage) and physical and social environmental characteristics were completed by 6,601 parents of children aged 3-13 years old and 3449 children aged 9-13 years old. In addition, 33 neighbourhood audits (systematic observations) were conducted to assess objective neighbourhood characteristics. Furthermore, a policy analysis was conducted in the four participating municipalities to provide an overview of the current local policy measures directed at stimulation of physical activity in children. Policy plans of six different policy sectors (Public Health, Sports, Education & Youth, Spatial Planning, Traffic & Transport, and Safety) were screened for their content on physical activity in children. In addition, semi-structured interviews were conducted with policy makers of each of these sectors to identify critical success factors in the development and realization of multi-sector policy plans aimed at stimulating physical activity in children. The results of all these research activities will be discussed with local policy makers during interactive workshop sessions in order to identify clear cut multi-sector policy measures that stimulate physical activity in children. Discussion This paper describes the study design of a project that focuses on multi-sector policy measures that stimulate physical activity in children. Next to extensive research into the environmental determinants of physical activity in children, much emphasis is placed on the translation of the research outcomes into concrete and feasible policy plans.